Some Dynamical Properties for the Logistic Map - Leonel, Edson Denis [UNESP] (My University, 2021)
Some dynamical properties for the logistic map will be discussed in this chapter. We start with the convergence to the fixed point at and near at the bifurcations. We use a set of scaling hypotheses and a homogeneous and generalized function to obtain a scaling law relating the critical exponents. A short discussion also on the route to chaos via period doubling is presented leading to the Feigenbaum exponents. A discussion on the Lyapunov exponent calculation for one-dimensional mappings is presented.